Anton 3: Twenty Microseconds of Molecular Dynamics Simulation Before Lunch - Shaw, David E.; Adams, Peter J.; Azaria, Asaph; Bank, Joseph A.; Batson, Brannon; Bell, Alistair; Bergdorf, Michael; Bhatt, Jhanvi; Butts, J. Adam; Correia, Timothy; Dirks, Robert M.; Dror, Ron O.; et al. (SC21: International Conference for High Performance Computing, Networking, Storage and Analysis, 2021)
Anton 3 is the newest member in a family of supercomputers specially designed for atomic-level simulation of molecules relevant to biology (e.g., DNA, proteins, and drug molecules). Anton 3 achieves order-of-magnitude improvements in time-to-solution over its predecessor, Anton 2 (the current state of the art), and is over 100-fold faster than any other currently available supercomputer, thereby enabling broad new avenues of research on critical questions in biology and drug discovery. This speedup means that a 512-node Anton 3 simulates a million atoms at over 100 microseconds per day. Furthermore, Anton 3 attains this performance while consuming an order of magnitude less energy per simulated microsecond than any other machine. Like its predecessors, Anton 3 was designed from the ground up around a new custom chip to best exploit the capabilities offered by new technologies. We present here the main architectural and algorithmic developments that were necessary to achieve such significant advances.